Etika Konsumsi Muslim: Tanggung Jawab Moral dalam Boikot Produk Pro-Zionisme Berdasarkan Analisis Kaidah Fiqhiyah - Wafa Syahidah; Unang Fauzi (TAFAQQUH, 2025)
This article aims to analyze the moral responsibility of Muslims in boycotting pro-Zionist products through the perspective of qaidah fiqhiyah (Islamic legal maxims). The study employs a qualitative approach with a literature review method, focusing on the principles of qaidah fiqhiyah and their application in the context of ethical consumption. The findings reveal that qaidah fiqhiyah, such as "dar'ul mafasid muqaddamun ‘ala jalbil mashalih" (preventing harm takes precedence over attaining benefits), can serve as a moral foundation for Muslims in making consumption-related decisions, including boycotting products that support activities contrary to Islamic values. This article contributes to the discourse on Muslim ethical consumption by offering a framework based on qaidah fiqhiyah that can be practically applied in global contexts, particularly concerning issues of social and political justice.